2001
DOI: 10.2165/00128072-200103010-00002
|View full text |Cite
|
Sign up to set email alerts
|

Management of Sepsis and Septic Shock in Infants and Children

Abstract: Sepsis and septic shock constitute an important cause of morbidity and mortality in critically ill children. Thus, the systemic response to infection and its management remains a major challenge in clinical medicine. Apart from antibiotic administration, the majority of available therapies are limited to supportive strategies, although considerable efforts are being undertaken to devise innovative approaches that modulate host inflammatory responses. In suspected sepsis, 2 or 3 days' empiric antibiotic therapy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 83 publications
(80 reference statements)
0
15
0
2
Order By: Relevance
“…During sepsis, the pathological production of inducible nitric oxide synthase (iNOS) and cyclooxygenase-2 (COX-2) may also have harmful effects on cardiomyocyte and impair cardiac contractile function (6,7). Interventions for sepsis involving anti-inflammatory agents have been demonstrated to reduce risk of cardiovascular complications (8,9).…”
Section: Introductionmentioning
confidence: 99%
“…During sepsis, the pathological production of inducible nitric oxide synthase (iNOS) and cyclooxygenase-2 (COX-2) may also have harmful effects on cardiomyocyte and impair cardiac contractile function (6,7). Interventions for sepsis involving anti-inflammatory agents have been demonstrated to reduce risk of cardiovascular complications (8,9).…”
Section: Introductionmentioning
confidence: 99%
“…Sepsis tends to peak at two primary times in the child's life and correspond to significant times in the maturity of the immune system (245). The first peak is in the neonate with an incidence of 4.3 per 1000 neonates.…”
Section: Pediatricsmentioning
confidence: 99%
“…Infants and young children are unable to increase myocardial contractility (i.e. stroke volume) 12,17 thus improving cardiac output can only be achieved by increasing heart rate. Frequently, tachycardia as a presenting feature of shock is thought to be a result of fever; however, the heart rate tends to rise by only 10 beats per minute for every Centigrade degree of pyrexia.…”
Section: Clinical Features Of Septic Shockmentioning
confidence: 99%
“…Some suggest colloid is more appropriate in situations of impaired capillary integrity 24–26 and reduces the volume required for resuscitation. A review of several studies showed that colloids also improve oxygen delivery, myocardial contractility and cardiac output 17 . Crystalloids on the other hand, are inexpensive and do not carry a risk of anaphylactoid reaction or infection.…”
Section: Fluidsmentioning
confidence: 99%
See 1 more Smart Citation